Implementasi Big Data terhadap Pengecekan Medis dan Konsultasi Kesehatan di Indonesia - Saudjhana, Audrey; Budiman, Arif; Fernando, Harley; Juliantio, Juliantio; Junianto, Kendy; Venessa, Kisusyenni; Salim, Steven; Tomy, Tomy (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2024)
The occurrence of the Covid-19 pandemic tests the resilience of the health service system in countries around the world, especially Indonesia, in responding and acting quickly and appropriately. This incident is a separate evaluation of the health service system in this country. As part of the global action plan to achieve Sustainable Development Goals (SDGs) point number 3, namely ensuring a healthy life and supporting welfare for all and efforts to improve public health as measured by the Public Health Development Index (IPKM), therefore, an increase in quality of health services is needed. The quality of health services includes issues of performance and affordability among society. With the development of innovations in database technology aspect, namely big data and artificial intelligence, it is hoped that this can be a breakthrough in the world of Indonesian health so that the goals of Indonesia in improving public health can be achieved.